Sol–Gel Synthesis of Translucent and Persistent Luminescent SiO2@ SrAl2O4 Eu, Dy, B Materials - Leimane, Madara; Krizmane, Katrina; Bite, Ivita; Grube, Jurgis; Vitola, Virginija (MDPI, 2023)
This publication offers an economically promising method of persistent luminescent silicate glass synthesis that does not involve high temperatures or ready-made (separately synthesized) PeL particles. In this study, we demonstrate the formation of SrAl2O4 doped with Eu, Dy, and B in a SiO2 glass structure using the one-pot low-temperature sol–gel synthesis method. By varying the synthesis conditions, we can use water-soluble precursors (e.g., nitrates) and a dilute aqueous solution of rare-earth (RE) nitrates as starting materials for SrAl2O4 synthesis, which can be formed during the sol–gel process at relatively low sintering temperatures (600 °C). As a result, translucent, persistently luminescent glass is obtained. The glass shows the typical Eu2+ luminescence and the characteristic afterglow. The afterglow duration is about 20 s. It is concluded that the slow drying procedure (2 weeks) is optimal for these samples to sufficiently get rid of the excess water (mainlyOH groups) and solvent molecules that can influence the strontium aluminate luminescence properties and have a pernicious effect on the afterglow. It can also be concluded that boron is playing a crucial role in the formation of trapping centers needed for PeL processes in the PeL silicate glass. © 2023 by the authors. --//-- Leimane M., Krizmane K., Bite I., Grube J., Vitola V.; Sol–Gel Synthesis of Translucent and Persistent Luminescent SiO2@ SrAl2O4 Eu, Dy, B Materials; (2023) Materials, 16 (12), art. no. 4416; DOI: 10.3390/ma16124416; https://www.scopus.com/inward/record.uri?eid=2-s2.0-85164191608&doi=10.3390%2fma16124416&partnerID=40&md5=244d1a722cbd9f56e3175d14b237ef79. Published under the CC BY 4.0 licence.
This research was funded by: ERDF PostDoc project No. 1.1.1.2/VIAA/3/19/440 (University of Latvia Institute of Solid State Physics, Latvia), L’ORéAL Baltic “For Women In Science” Program with the support of the Latvian National Commission for UNESCO and the Latvian Academy of Sciences, and M.L. acknowledges the support of “Mikrotīkls”, University of Latvia Foundation and Latvian Science Council project lzp-2021/1-0215, The Institute of Solid State Physics, University of Latvia, as the Center of Excellence, has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01- 2016–2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; glass; persistent luminescence; sol–gel synthesis